PENGARUH PEMBELAJARAN PAI MULTIKULTURAL TERHADAP SIKAP TOLERANSI MAHASISWA PRODI PAI UNIVERSITAS ISLAM MALANG - Ria Dwi Rahmawati Ashari; Anwar Sa’dullah; Fita Mustafida (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The life of college students that we witness is they often first putting their emotional behavior, discriminating skin color, being in a toxic friendship circle, and being inconsiderate. Those acts are considered a lack of understanding of differences and diversities. It is crucial to foster social tolerance among the students through the Multicultural Islamic Studies as a Mandatory study program. This study aims to determine the influence of multicultural Islamic education studies on students' social tolerance in the Islamic Education Study program at the University of Islam Malang. The type of this research is quantitative descriptive with questionnaires, interviews, and documentation as data collection techniques, and the data analysis is carried out by testing the hypothesis using the r-test and t-test with the SPSS program. The results of the t-test are 8,912 > 2,00 (t-table) with a significance level of 0,000 < 0,05. Then, there is an effect of the independent variable on the dependent variable. The results of the r-test are 0,578 (57,8%), then the percentage of Multicultural Islamic Education Studies learning (X) affects student tolerance (Y) of 57.8% simultaneously. Based on the value of the r-test, t-test, and significance, it can be concluded that the hypothesis in this study rejects (Ho) and accepts (Ha), that there is a significant effect of Multicultural Islamic Studies learning on the tolerance of students of Faculty of Islamic Religion, Islamic Studies Study Program, University of Islam Malang.